2019
DOI: 10.1103/physrevb.100.195404
|View full text |Cite
|
Sign up to set email alerts
|

Conformal transformation of Dyakonov surface waves into bound states of cylindrical metamaterials

Abstract: We put forward the use of transformation optics to map surface waves that exist as one-dimensional modes supported by anisotropic structures into bound states in twodimensional geometries. Specifically, we show the conformal mapping of Dyakonov waves existing in infinite planar surfaces separating birefringent media into bound modes supported by a cylindrical structure made of suitable metamaterials. In contrast with the original Dyakonov waves, the resulting fiber-like modes are highly dispersive, may exist a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
9
0
1
Order By: Relevance
“…При этом анализировались лишь некоторые частные случаи границ раздела двуосных кристаллов при относительно простых пространственных ориентациях их оптических осей. Кроме того, в литературе изучались и другие разновидности волн Дьяконова, существование которых возможно на границах раздела других типов веществ, таких, как гиперболические, хиральные и бианизотропные материалы [16][17][18][19], а также возникающих в ограниченных средах [20][21][22][23].…”
Section: Introductionunclassified
“…При этом анализировались лишь некоторые частные случаи границ раздела двуосных кристаллов при относительно простых пространственных ориентациях их оптических осей. Кроме того, в литературе изучались и другие разновидности волн Дьяконова, существование которых возможно на границах раздела других типов веществ, таких, как гиперболические, хиральные и бианизотропные материалы [16][17][18][19], а также возникающих в ограниченных средах [20][21][22][23].…”
Section: Introductionunclassified
“…Very recently, a practically important case of Dyakonov-like surface waves in finite-size resonator structures has been studied for cylindrical waveguides [34,35] as well as for flat interfacial strip waveguides [36,37]. It has been demonstrated that due to a non-zero curvature of cylindrical waveguides, Dyakonov surface waveguide modes (DSWMs) in them inevitably have radiative losses.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [ 29] it has been shown that the Dyakonov surface waves can be conformally transformed into the bound states of cylindrical metamaterials. Dyakonov-like surface waves have been also theoretically predicted in anisotropic cylindrical waveguides.…”
Section: Introductionmentioning
confidence: 99%